Gut microbial alterations associated with the exacerbation of experimental autoimmune uveitis in PGRN-deficient mice - Zhou, Wenjun; Zhang, Song; Wang, Chaokui (Frontiers in Immunology, 2026)
PurposeProgranulin (PGRN) has been shown to play a protective role in the development of a variety of immune-mediated diseases, and the gut microbiome has been implicated in the pathogenesis of autoimmune diseases. In this study, we investigate the changes in the gut microbiota and their association with the severity of experimental autoimmune uveitis (EAU) in PGRN-deficient mice.MethodsWT and PGRN-deficient C57BL/6 mice were used to induce EAU using interphotoreceptor-binding protein peptide. Gastrointestinal (GI) contents collected from both groups of induced EAU were subjected to 16S rRNA gene sequencing analysis.ResultsPGRN-deficient mice developed exacerbated EAU compared to wild-type (WT) mice. The microbial richness of the GI contents in PGRN-deficient EAU mice was significantly lower than in WT mice. The PGRN-deficient EAU mice showed a significantly reduced microbial abundance in five phyla, namely, Cyanobacteria, Epsilonbacteraeota, Firmicutes, Nitrospirae, and Patescibacteria, and a significantly increased abundance in the other four phyla, namely, Deferribacteres, Proteobacteria, Spirochaetes, and Tenericutes. More importantly, a newly emerged phylum named Chlamydiae was detected in the gut microbial community of PGRN-deficient EAU mice. The histopathological scores were significantly negatively correlated with gut microbial abundance and significantly positively correlated with chlamydial abundance.ConclusionOur results showed that PGRN plays a protective role in EAU, and the significant changes in the gut microbiome may be associated with the exacerbation of inflammation in the PGRN-deficient EAU mice.